Enhancing the Capacity of School Nurses to Reduce Excessive Anxiety in Children: Development of the CALM Intervention. Issue 3 (14th July 2015) - Drake, Kelly L.; Stewart, Catherine E.; Muggeo, Michela A.; Ginsburg, Golda S.
<x xml:space="preserve">Abstract</x> Problem Excessive anxiety is among the most common psychiatric problems facing youth. Because anxious youth tend to have somatic complaints, many seek help from the school nurse. Thus, school nurses are in an ideal position to provide early intervention. This study addresses this problem and describes the plans to develop and test a new intervention (Child Anxiety Learning Modules; CALM), delivered by school nurses, to reduce child anxiety and improve academic functioning. Methods An iterative development process including consultation with an expert panel, two open trials, and a pilot randomized controlled study comparing CALM to usual care is proposed. Feedback will be solicited from all participants during each phase and data on outcome measures will be provided by children, parents, teachers, and independent evaluators. Findings Data will be collected on intervention satisfaction and feasibility. Primary outcomes that include child anxiety symptoms, classroom behavior, and school performance (e.g., attendance, grades, standardized test scores) will be collected at pre‐ and post‐interventions and at a 3‐month follow‐up evaluation. Conclusions Pediatric anxiety is a common problem that school nurses frequently encounter. Consequently, they are well positioned to play a key role in enhancing access to behavioral health interventions to reduce anxiety and may therefore make a significant positive public health impact.